Toronto the Good? : Negotiating Race in the Diverse City. - Almeida, Shana. (University of Toronto Press, 2022)
Toronto the Good?uniquely explores what diversity does to remake the City of Toronto as a beacon of democracy, racial inclusion, and progress.